Factors influencing the effective use of technology among Malaysian teachers - Samy, Naresh Kumar; Che Rose, Raduan; Alby, Jeffrey Lawrence D'Silva (Eurojournals, 2008)
Previous studies revealed that the socio-demographic factors are vital and would sway the actual usage of computer (AUC) among secondary school teachers. Nevertheless the outcome of previous studies had shown inconsistent results. Hence, it is pertinent to investigate further on the influence of socio-demographic factors of gender, age, teaching experience, main subject taught, and training in computer usage on AUC among secondary school teachers. The AUC means the intensity of the computer usage by teachers, which would be measured in terms of how frequently the computer is used for job related and personal tasks. Interestingly this study has been carried out in Malaysia seeing that numerous incentives and support were given to the Mathematics, Science and English language (MSE) teachers to use computer in schools but preliminary observations found that they are not fully making use of the investment in technology.